The Effect of the Effectiveness of Ease of Use and Customer Satisfaction on Customer Loyalty of Bank Sumut Mobile Banking Users in Medan City - Elisa Emeliya Sihombing; Kartini Harahap (PT FORMOSA CENDEKIA GLOBAL, 2023)
FinTech developments are increasing, one of which is the creation of Mobile Banking, where currently people use this application to make daily transactions easier and more practical. This research was conducted to see the effect of the effectiveness of ease of use and Customer Satisfaction on customer loyalty of North Sumatra bank mobile banking users in the city of Medan. This research uses quantitative research methods with an associative approach, and uses non-probability sampling with purposive sampling and 100 respondents, using several tests managed with SPSS. The results of this research show that the variables ease of use and customer satisfaction have an influence simultaneously on the customer loyalty variable of 0.000 < 0.05 and the Fcount value obtained is 48.2% and 52.8%. the rest is influenced by factors outside this research model.